Anurogryllus Saussure, 1877 (Orthoptera: Gryllidae: Gryllinae) from southern Brazil: new species and new records - Redü, Darlan Rutz; Zefa, Edison (Zootaxa, 2017)
The aim of this work was to extend the taxonomic knowledge of the species of Anurogryllus Saussure, 1877 that occurs in the southern municipalities of Rio Grande do Sul State, Brazil. We found three different species, Anurogryllus tapes sp. nov. collected in municipalities of Canguçu and Capão do Leão, Anurogryllus patos sp. nov. from Capão do Leão and Anurogryllus toledopizai (de Mello, 1988) recorded from Canguçu, Capão do Leão e São Lourenço do Sul. Here we present the descriptions of morphology, male genitalia and calling songs.